Building Confidence in Simulation: Applications of EasyVVUQ. Issue 8 (15th June 2020) - Wright, David W.; Richardson, Robin A.; Edeling, Wouter; Lakhlili, Jalal; Sinclair, Robert C.; Jancauskas, Vytautas; Suleimenova, Diana; Bosak, Bartosz; Kulczewski, Michal; Piontek, Tomasz; Kopta, Piotr; Chirca, Irina; et al.
Abstract: Validation, verification, and uncertainty quantification (VVUQ) of simulation workflows are essential for building trust in simulation results, and their increased use in decision‐making processes. The EasyVVUQ Python library is designed to facilitate implementation of advanced VVUQ techniques in new or existing workflows, with a particular focus on high‐performance computing, middleware agnosticism, and multiscale modeling. Here, the application of EasyVVUQ to five very diverse application areas is demonstrated: materials properties, ocean circulation modeling, fusion reactors, forced human migration, and urban air quality prediction. Abstract : Validation, verification, and uncertainty quantification (VVUQ) of simulations is essential for encouraging their adoption within decision‐making processes. The EasyVVUQ Python library is designed to facilitate implementation of advanced VVUQ techniques in scientific workflows. The library is here applied to examples from five diverse research domains: materials properties, ocean circulation modeling, fusion reactors, forced human migration, and urban air quality prediction.